Art, research, philosophy - Cazeaux, Clive (Routledge, 2017)
Art, Research, Philosophy explores the emergent field of artistic research: art produced as a contribution to knowledge. As a new subject, it raises several questions: What is art-as-research? Don't the requirements of research amount to an imposition on the artistic process that dilutes the power of art? How can something subjective become objective? What is the relationship between art and writing? Doesn't description always miss the particularity of the artwork?